A metal oxide TFT gate driver with a single negative power source employing a boosting module. Issue 1 (2nd January 2020) - Xu, Yan-Gang; Chen, Jun-Wei; Xu, Wen-Xing; Zhou, Lei; Wu, Wei-Jing; Zou, Jian-Hua; Xu, Miao; Wang, Lei; Peng, Jun-Biao
Abstract : This paper presents a new gate driver integrated by In-Zn-O thin-film transistors (IZO TFTs) with the etch stop layer (ESL) structure, in which only a single negative power source is used on account of a new boosting module. The boosting module is controlled only by the VIN signal for generating a lower level than VSS. The proposed gate driver with 15 stages is fabricated through the IZO TFT process on a glass substrate to verify its function. The experiment results showed that the proposed gate driver can successfully output full-swing waveforms with resistive load RL =2 kΩ and capacitive load CL =30 pF at the 16.7 and 66.7 kHz clock frequencies, and can also output as small as 3.2 μs pulse width with little distortion, revealing good stability.